Analysis of the Needs for the Development of Computational Chemistry-Based Learning Media on the Subject of Hydrocarbons - Gustiana, Rara; Nugraha, Asep Wahyu; Nurfajriani, Nurfajriani (LAVOISIER: Chemistry Education Journal, 2024)
AbstractThis study aims to analyze the needs before developing computational chemistry-based learning media on hydrocarbon materials. This research is classified as development research developed with the ADDIE model. It's just that the stage used in this study is only limited to the analysis stage. Data collection in research is carried out by literature study methods and field studies with research instruments in the form of questionnaires on learning media needs and interviews by teachers. The location of this study is SMA Negeri Modal Bangsa Arun. Based on the results of interviews with chemistry teachers, it was found that learning hydrocarbon material at the high school level requires more effort because students must understand molecular structure, chemical bonds, and atomic structure. This makes students less understanding of concepts microscopically and can also cause misconceptions. Then, the results of the needs analysis show that there are still limited learning media that support microscopic concepts, especially the shape of molecules in 3-D. Based on the results of this study, it can be concluded that it is necessary to develop computational chemistry-based learning media on hydrocarbon materials.